Intersectionalities and access in fieldwork in postconflict Liberia: Motherland, motherhood, and minefields. Issue 470 (9th October 2018) - Yacob-Haliso, Olajumoke
Abstract: This research note interrogates the varied ways in which researcher and research subjects' intersectional identities complicate multiple levels of access to research participants, specifically with respect to research I conducted with refugee women who returned to Liberia after the end of the civil war in 2003. I argue that motherland (or nationality) and motherhood (or maternity) produce 'minefields' during fieldwork that a researcher has to navigate in achieving different levels of access to research subjects, particularly in postconflict situations. While the literature mostly discusses these issues from the perspective of non-Africans conducting fieldwork abroad, this essay analyses issues arising from being a young, female Nigerian conducting research with women, mostly mothers, in the same African sub-region. It explains how being a young, married, pregnant, and mothering Nigerian facilitated or obstructed access to research participants. This foregrounds the complexity of the insider/outsider debate for researchers conducting fieldwork in various contexts, and thereby contributes to the wider literatures on feminist methodologies and qualitative fieldwork.